2012
DOI: 10.1371/journal.pntd.0001936
|View full text |Cite
|
Sign up to set email alerts
|

Clofazimine Modulates the Expression of Lipid Metabolism Proteins in Mycobacterium leprae-Infected Macrophages

Abstract: Mycobacterium leprae (M. leprae) lives and replicates within macrophages in a foamy, lipid-laden phagosome. The lipids provide essential nutrition for the mycobacteria, and M. leprae infection modulates expression of important host proteins related to lipid metabolism. Thus, M. leprae infection increases the expression of adipophilin/adipose differentiation-related protein (ADRP) and decreases hormone-sensitive lipase (HSL), facilitating the accumulation and maintenance of lipid-rich environments suitable for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…We and others have previously shown that the inhibition of LD formation in ML‐ and BCG‐infected cells reduces bacterial viability (D'Avila et al ., ; Almeida et al ., ; Mattos et al ., 2011b). Moreover, a recent report has suggested that clofazimine, one of the drugs that compose the WHO‐MDT regimen for leprosy treatment, exerts its microbicidal activity via the decreasing LD accumulation in infected cells (Degang et al ., ). Interestingly, besides its classical mechanistic action of inhibiting the HMGCR, lovastatin was able to decrease LDL‐Cho uptake in ML‐infected macrophages, corroborating with the literature data (Aviram et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…We and others have previously shown that the inhibition of LD formation in ML‐ and BCG‐infected cells reduces bacterial viability (D'Avila et al ., ; Almeida et al ., ; Mattos et al ., 2011b). Moreover, a recent report has suggested that clofazimine, one of the drugs that compose the WHO‐MDT regimen for leprosy treatment, exerts its microbicidal activity via the decreasing LD accumulation in infected cells (Degang et al ., ). Interestingly, besides its classical mechanistic action of inhibiting the HMGCR, lovastatin was able to decrease LDL‐Cho uptake in ML‐infected macrophages, corroborating with the literature data (Aviram et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…BDQ is an inhibitor of the F 1 /F o ATP synthase, and CLO is thought to be reduced by the mycobacterial type 2 NADH:quinone oxidoreductase (NDH-2) enzyme, leading to a CLO-mediated increase in NADH oxidation and reactive oxygen species (ROS) production (12,13). Other studies have also reported that CLO may act on the lipids of the bacterial cell wall, as observed in macrophages infected with M. leprae (14). On the other hand, there were compounds targeting the ETC, such as LPZs, which were not synergistic when combined with MCZ in vitro (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Besides ADRP and perlipin expression in infected cells, confirming the induction of lipid droplets in leprosy, it was shown that M. leprae ‐infected macrophages have a reduced expression of hormone‐sensitive lipase, which would help to increase intracellular lipid accumulation, favoring bacterial survival . Recently, a study on the influence of drugs used in leprosy MDT (dapsone, clofazimine and rifampicin) showed that clofazimine, but not dapsone or rifampicin, modulates lipid metabolism in infected THP‐1 cells, decreasing the expression of ADRP and increasing hormone‐sensitive lipase in M. leprae ‐infected cells . In the case of the patients studied in this work, all were submitted to standard MDT for multibacillary leprosy, which includes clofazimine.…”
Section: Discussionmentioning
confidence: 99%
“…[42,43] Recently, a study on the influence of drugs used in leprosy MDT (dapsone, clofazimine and rifampicin) showed that clofazimine, but not dapsone or rifampicin, modulates lipid metabolism in infected THP-1 cells, decreasing the expression of ADRP and increasing hormonesensitive lipase in M. leprae-infected cells. [44] In the case of the patients studied in this work, all were submitted to standard MDT for multibacillary leprosy, which includes clofazimine. Therefore, the lipid changes observed in the skin after treatment may be partially attributed to the effect of clofazimine on infected macrophages.…”
Section: Discussionmentioning
confidence: 99%